Hare Krishna mantra in Prague streets: The sacred, music and trance - Jurková, Zuzana; Seidlová, Veronika (Lidé města, 2011)
The article introduces one of the regular outdoor musical events in Prague – the harinam, a procession of Hare Krishna devotees. This event is set in the broader context of music as an integral part of religious rituals and/or holidays. The universal connection of music and spirituality is found in two extreme positions: as culturally determined or as universalistic/objectivistic. One of the traditions that understand spirituality as intrinsically present in music and thus the connection of the sacred and music as objective, is an Indian tradition. Its two basic approaches, that is, the Vedic “Apollonian” concept and the “Dionysian” concept, present in various directions, e.g., Tantrism, are actually present in the Hare Krishna procession. Our attention is drawn to the interpretation of the strikingly culturally specific elements of this “Dionysian” stream. Using Judith Becker’s (2004) concept of trance, the Prague harinam shows itself to be like a culturally conditioned form of universal models of spiritual music.